2011
DOI: 10.1007/s00436-011-2280-0
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes-based resistant mechanism in pyrethroid resistant and susceptible Aedes aegypti strains from northern Thailand

Abstract: Previous studies have shown that permethrin resistance in our selected PMD-R strain of Aedes aegypti from Chiang Mai, Thailand, was associated with a homozygous mutation in the knockdown resistance (kdr) gene and other mechanisms. In this study, we investigated the metabolic mechanism of resistance of this strain compared to the PMD strain which is susceptible to permethrin. The permethrin susceptibility of larvae was determined by a dose-response bioassay. Two synergists, namely piperonyl butoxide (PBO) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…In mammals, the oxidation of pyrethroids was catalysed by ALDH [16]. A study in insecticide metabolism revealed the important role of ALDH in the detoxification of pyrethroid in mosquito [20]. Multiple detoxification enzymes were identified as a target of pyrethroid activity-based probes in rat proteome, including P450s, UDP-glucuronosyltransferases, Flavin-containing monooxygenase and ALDH [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, the oxidation of pyrethroids was catalysed by ALDH [16]. A study in insecticide metabolism revealed the important role of ALDH in the detoxification of pyrethroid in mosquito [20]. Multiple detoxification enzymes were identified as a target of pyrethroid activity-based probes in rat proteome, including P450s, UDP-glucuronosyltransferases, Flavin-containing monooxygenase and ALDH [45].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti , it has been reported that parental permethrin can be hydrolysed in vitro. Our previous study demonstrated that the formation of PBacid was decreased in the presence of an esterase inhibitor, BNPP, suggesting the function of esterases in permethrin metabolism [20]. The importance of particular CEs in pyrethroid detoxification has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two ALDH genes, ALDH9948 and ALDH14080 were upregulated in the PMD-R strain and both recombinant proteins showed oxidase activity against phenoxybenzyl aldehyde, an aldehyde moiety of pyrethroid (Lumjuan et al, 2014). The addition of piperonyl butoxide (PBO), an oxidase inhibitor, to larval bioassays of both PMD-R and F/C 1534 heterozygous individuals reduced permethrin resistance by ~3 fold and ~8 fold, respectively (Yanola et al, 2010;Somwang et al, 2011). Permethrin resistance in the PMD-R strain is conferred mainly by the F1534C mutation with oxidative enzymes playing a partial role in overall resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, excessive and continuous application of pyrethroids has caused the development of pyrethroid resistance, which has become the major obstacle to control the mosquito borne diseases. The mechanisms responsible for pyrethroid resistance are mainly associated with target site modification and metabolic resistance (Bouvier et al 2002; Somwang et al 2011). Overexpression and/or elevated activity of P450s may enhance biodegradation of the pyrethroids (Lertkiatmongkol et al 2011).…”
Section: Introductionmentioning
confidence: 99%